2021
DOI: 10.1002/anie.202103295
|View full text |Cite
|
Sign up to set email alerts
|

Na9Bi5Os3O24: A Diamagnetic Oxide Featuring a Pronouncedly Jahn–Teller‐Compressed Octahedral Coordination of Osmium(VI)

Abstract: The Jahn-Teller (JT) theorem constitutes one of the most fundamental concepts in chemistry.Intransition-element chemistry,t he 3d 4 and 3d 9 configurations in octahedral complexes are particularly illustrative,w here ad istortion in local geometry is associated with ar eduction of the electronic energy.However,there has been alasting debate about the fact that the octahedra are found to exclusively elongate.I n contrast, for Na 9 Bi 5 Os 3 O 24 ,t he octahedron around Os 6+ (5d 2 ) is heavily compressed, lifti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…[9][10][11][12][13][14][15][16][17][18][19][20][21] Recently, it has been demonstrated that even without any structural constraints, osmium(VI) adopts an intrinsic non-magnetic ground state in Na 9 Bi 5 Os 3 O 24 : as a consequence of strong Jahn-Teller compression of the [OsO 6 ] 6À octahedra, the degeneracy of the t 2g level (d xy , d yz and d xz ) is lifted, even overcoming Hund's coupling for a t 2g system. [22] This finding further explains the diamagnetic properties of Na 2 OsO 4 , which features similar axially compressed octahedra. [23] In most of the work published on oxo-osmates(VI) the double perovskite (DP) type of structure, A 2 BB'O 6 , has been in the focus, which is a particularly robust matrix allowing for a rich diversity of cationic combinations.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…[9][10][11][12][13][14][15][16][17][18][19][20][21] Recently, it has been demonstrated that even without any structural constraints, osmium(VI) adopts an intrinsic non-magnetic ground state in Na 9 Bi 5 Os 3 O 24 : as a consequence of strong Jahn-Teller compression of the [OsO 6 ] 6À octahedra, the degeneracy of the t 2g level (d xy , d yz and d xz ) is lifted, even overcoming Hund's coupling for a t 2g system. [22] This finding further explains the diamagnetic properties of Na 2 OsO 4 , which features similar axially compressed octahedra. [23] In most of the work published on oxo-osmates(VI) the double perovskite (DP) type of structure, A 2 BB'O 6 , has been in the focus, which is a particularly robust matrix allowing for a rich diversity of cationic combinations.…”
Section: Introductionmentioning
confidence: 58%
“…As to be expected, the effective magnetic moments in respective oxo‐osmates(VI) are lower than the spin‐only value, however, the wide spread of the reported experimental values (ranging from 0 to 2.1 μ B ) is puzzling. 9–21 Recently, it has been demonstrated that even without any structural constraints, osmium(VI) adopts an intrinsic non‐magnetic ground state in Na 9 Bi 5 Os 3 O 24 : as a consequence of strong Jahn‐Teller compression of the [OsO 6 ] 6− octahedra, the degeneracy of the t 2 g level ( d xy , d yz and d xz ) is lifted, even overcoming Hund's coupling for a t 2 g system [22] . This finding further explains the diamagnetic properties of Na 2 OsO 4 , which features similar axially compressed octahedra [23] …”
Section: Introductionmentioning
confidence: 99%
“…Ti 4+ cation has an outer electronic configuration of 3 d 0 , and it can obtain electrons from the filled 2 p orbital of aligned O 2– through pd hybridization (covalent bond of 3 d 0 (Ti 4+ ) – 2 p 6 (O 2– )). The extra electron undergoes the second-order Jahn–Teller (JT) distortion and the degeneracy of the d orbital, which further compresses the Ti 4+ O 6 octahedron in the [110] direction. ,, Similarly, some M 3+ cations would also get electrons from the aligned O 2– as well. The second-order JT effect on the intra-octahedral distortion decreases in the order of Cr 3+ ( t 2g 3 ) > Al 3+ ( d 0 ) > Fe 3+ ( t 2g 3 e g 2 ), which is not obvious for the other M 3+ O 6 octahedra (M = Ni, Co, Ga, and Mn) …”
Section: Resultsmentioning
confidence: 99%
“…There are several factors affecting the incorporation of cations, including pressure, temperature, oxygen fugacity, , and the sizes of the doped cations . First-principles calculation is also utilized in the present study to examine the role of the intra-octahedral distortion in M 3+ substitution, , as well as its effect on the optical properties.…”
Section: Introductionmentioning
confidence: 99%